CHILDHOOD ISSUE IN THE NATIONAL SCIENTIFIC THOUGHT (1900-1918) - Світлана Лупаренко (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The preconditions for national scholars' increased interest in research of childhood issues in 1900-1918 are determined. They are awareness of child and childhood uniqueness by the world community, lack of knowledge of childhood nature, society's need for educated employees in different industry sectors. Childhood research directions are revealed. They are physiological (age peculiarities of physical development, child reflexes, motor activity), psychological and pedagogical (age peculiarities of mental development, ideas of free education, family education, physical education, child's health), ethnographical (children's way of life, folklore) researches.